Power, gender, and leadership in international sport organizations: a systematic literature review - Anisa Sholiha Mia; Ifdil Ifdil; Andre Igoresky (IICET (Indonesian Institute for Counseling, Education and Therapy), 2025)
In international sport organisations, governance is still heavily male-dominated. This persists despite years of gender equality pledges and more women taking part in sports. In this systematic literature review, we looked at recent empirical evidence on women's representation in sport governance. We examined the barriers and enablers that affect their access to leadership. We also looked at how organisations either maintain or challenge gendered power structures. Following the PRISMA 2020 guidelines, this systematic literature review searched the Scopus database for empirical studies published between 2015 and 2025 using a structured Boolean strategy. Two independent reviewers conducted study screening and data extraction, resolving disagreements through discussion. The methodological quality of eligible studies was assessed using the FICO framework, and evidence was synthesised through thematic synthesis. From 374 identified records, 73 full-text articles were assessed for eligibility, and ten studies met all inclusion and quality criteria for the final synthesis. Four main themes came out. First, women are still underrepresented on sport boards. Very few organisations hit the 30% mark that's linked to having real influence. Second, structural and cultural barriers keep limiting leadership chances. These include hegemonic masculinity, homologous reproduction, biased selection practices, and the glass ceiling. Third, coercive tools like gender quotas and board mandates lead to more consistent representation gains than voluntary efforts. But cultural change stays limited. Fourth, equity champions and gender-equality committees can help push progress forward. Yet they often bump into wider organisational constraints. These results back up critical mass theory, feminist institutionalism, and gendered-organisation perspectives. They also show that hitting numerical targets is not enough. We need structural and cultural reforms too. Future work should focus on intersectional, longitudinal, and non-Western angles.